Cerebrospinal Fluid IgM Levels in Association With Inflammatory Pathways in Multiple Sclerosis Patients - Magliozzi, Roberta; Mazziotti, Valentina; Montibeller, Luigi; Pisani, Anna I.; Marastoni, Damiano; Tamanti, Agnese; Rossi, Stefania; Crescenzo, Francesco; Calabrese, Massimiliano (Frontiers in Cellular Neuroscience, 2020)
Background: Intrathecal immunoglobulin M (IgM) synthesis has been demonstrated in multiple sclerosis (MS) since early disease stages as predictor factor of worse disease course. Similarly, increased cerebrospinal fluid (CSF) molecules related to B cell intrathecal activity have been associated with a more severe MS progression. However, whether CSF levels of IgM are linked to specific inflammatory and clinical profile in MS patients at the time of diagnosis, remains to be elucidated. Methods: Using customized Bio-Plex assay, the protein levels of IgG, IgA, IgM and of other 34 inflammatory molecules, related to B-cell, T-cell and monocyte/macrophage activity, were analysed in the CSF of 103 newly diagnosed relapsing-remitting MS patients and 36 patients with other neurological disorders. CSF IgM levels were also correlated with clinical and neuroradiological measures (advanced 3T-MRI parameters), at diagnosis and after 2 years of follow-up. Results: A 45.6% increase in CSF IgM levels was found in MS patients compared to controls (p=0.013). CSF IgM levels correlated with higher CSF levels of CXCL13 (p=0.039), CCL21 (p=0.023), IL-10 (p=0.025), IL-12p70 (p=0.020), CX3CL1 (p=0.036) and CHI3L1 (p=0.048) and were associated with earlier age of patients at diagnosis (p=0.008), white matter lesions (WMLs) number (p=0.039) and disease activity (p=0.033) after 2 years of follow-up. Conclusion: IgM are the immunoglobulins mostly expressed in the CSF of naïve MS patients compared to other neurological conditions at the time of diagnosis. The association between increased CSF IgM levels and molecules related to both B-cell immunity (IL-10) and recruitment (CXCL13 and CCL21) and to macrophage/microglia activity (IL-12p70, CX3CL1 and CHI3L1) suggests possible correlation between humoral and innate intrathecal immunity in early disease stage. Furthermore, the association of IgM levels with WMLs and MS clinical and MRI activity after 2 years supports the idea of key role of IgM in the disease course.